Estrutura Genética do Germoplasma de Prunus persica (L.) Batsch no Brasil - Thurow, Liane Bahr (2013)
Based on the advanced knowledge in genomic, marker-assisted selection shows up as a promising strategy especially to accelerate the development of new cultivars in perennial species, such as peach. In this context, this dissertation addressed the current situation and the prospects of using marker-assisted selection in peach breeding programs as well as to characterize the genetic variability and population structure of an association panel representative of peach germplasm available in Brazil through SSR analysis. Based on a literature review, it was seen that a high number of QTL (Quantitative Trait Loci) is identified in genetic maps of peach, but, despite the importance of the characters studied, the use of markerassisted selection has been incipient by breeding programs. By the other side, with the recent completion of the sequencing of the peach genome, the perspective is that the low use of molecular tools by peach breeding program will change in the coming years. In this trend, the genetic variability present in the association panel representative of peach germplasm in Brazil is quite relevant. On the other hand, this germplasm is structured into two subpopulations according to the fruit flesh type, melting or non-melting, with some genotypes being a mixture of both types of fruit flesh. Greater variability is available in the melting flesh group. These results show that the association panel is suitable for association studies given its relevant genetic variability. However, it should be taken into account in the association studies the genetic structure intrinsic to this germplasm to avoid the identification of false markertrait associations.